100‐nm thick single‐phase wurtzite BAlN films with boron contents over 10%. Issue 8 (11th January 2017) - Li, Xiaohang; Wang, Shuo; Liu, Hanxiao; Ponce, Fernando A.; Detchprohm, Theeradetch; Dupuis, Russell D.
Abstract : Growing thicker BAlN films while maintaining single‐phase wurtzite structure and boron content over 10% has been challenging. In this study, we report on the growth of 100 nm‐thick single‐phase wurtzite BAlN films with boron contents up to 14.4% by MOCVD. Flow‐modulated epitaxy was employed to increase diffusion length of group‐III atoms and reduce parasitic reactions between the metalorganics and NH3 . A large growth efficiency of ∼2000 μm mol −1 was achieved as a result. Small B/III ratios up to 17% in conjunction with high temperatures up to 1010 °C were utilized to prevent formation of the cubic phase and maintain wurtzite structure.